Female labour participation rates in Norway - trends and cycles - Ingvild Svendsen (Statistics Norway, Research Department, 1999)
Norwegian female labour participation rates have increased steadily since the beginning of the seventies. This paper address several issues concerning female labour participation series for the period 1972-1997. The main purpose is to identify factors that explain the trend-like increase during the last 25 years and a possible cyclical component that is due to labour market conditions. The resulting relations for women in the age-groups 25-39 years and 40-59 years include long-run effects from wages, education and a significant cyclical component. The wage elasticity is the same for the two groups by restriction. For the older women (60-66 years) we find a higher wage elasticity. Children have a negative impact on the labour supply for female 25-39 years. We get no significant effects from the extension of the parental leave and day-care coverage.
Keywords: C22; C32; J22; 330; Female labour participation rates; discouraged worker; lifetime effects; time series.